Public policy analysis in tourism security of Romblon, the Philippines: Potentials, challenges, issues, and constraints of a multi-islands province - Andalecio, Avi Ben P. (School of Tourism, Universitas Ciputra Surabaya, 2024)
The Province of Romblon located in the very heart of the Philippines is home to various tourism resources. However, despite the positioning of the province as a destination, public policies like sound tourism master plans are inexistent to safeguard sustainability in the province and its LGUs. The main objective of study is focused on digging deep into the debates and arguments about CBT trend in the Philippines and examine its potential as a strategy in a multi-island province of Romblon, a province which lacks a localized public policy and strategy regarding Community-Based Tourism ventures. Findings reveal that tourism plays an important role in community development, community engagement, and citizen participation.